2016
DOI: 10.1080/08820139.2016.1250219
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Attenuates Lipopolysaccharide/Galactosamine-induced Acute Liver Failure by Antagonizing Hepatic Inflammation and Apoptosis

Abstract: Bacterial lipopolysaccharide (LPS)-induced acute liver failure (ALF) is a common severe clinical syndrome in intensive care unit. No other methods are available for its prevention apart from supportive treatment and liver transplantation. Tamoxifen (TAM) was reported to attenuate ALF induced by excessive acetaminophen, while its effect on LPS-induced ALF remained unknown. For this, in the present study, we comprehensively assessed whether TAM can attenuate ALF induced by LPS/galactosamine (GaIN). Mice were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Activation of TLR4 signaling in Kupffer cells may subsequently initiate inflammatory pathways that promote hepatocyte injury, cholestasis, apoptosis and necrosis, as well as activation of stellate cells ( 26 , 27 ). An in vitro study indicated that chenodeoxycholic acid and GW4064, two FXR agonists, rescued HepG2 cells from serum deprivation-induced apoptosis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TLR4 signaling in Kupffer cells may subsequently initiate inflammatory pathways that promote hepatocyte injury, cholestasis, apoptosis and necrosis, as well as activation of stellate cells ( 26 , 27 ). An in vitro study indicated that chenodeoxycholic acid and GW4064, two FXR agonists, rescued HepG2 cells from serum deprivation-induced apoptosis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell death plays an important role in ALF [ 26 , 27 ]. Apoptosis is a form of hepatocyte death that contributes to ALF [ 28 , 29 ]. Evidence of apoptotic pathways was identified in our transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%